Pengaruh Persepsi Harga, Diskon, dan Customer Experience terhadap Loyalitas Pelanggan Produk Fashion Shopee - Eka Susilawati; Estik Hari Prastiwi; Yulyar Kartika (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2022)
This study was conducted to determine and analyze the effect of price perception, discount, and customer experience on customer loyalty for fashion products at Shopee.This research was carried out with a quantitative descriptive method using primary data obtained through questionnaires and interviews. The population in this study were students of the Faculty of Economics and Business, University of 17 August 1945, Surabaya. The sample in this study was 72 students using the purposive sampling method because this method uses a sampling technique with certain considerations or criteria. The data analysis technique used in this research is multiple regression analysis methods using the Statistical Product and Service Solution (SPSS) version 26 program. The results of this study indicate that the price perception variable has a positive and significant effect on customer loyalty. The discount variable has a positive and significant effect on customer loyalty. The customer experience variable has a significant positive effect on customer loyalty. From the research results, it is known that the effect of price perception, discount, and customer experience partially or jointly has a significant positive effect on customer loyalty.Keywords: Price Perception, Discount, Customer Experience, and Customer Loyalty